Copper (II)-catalysed direct conversion of aldehydes into nitriles in acetonitrile. (1st August 2017) - Ma, Xiaoyun; Ao, Jun; Chen, Zhengjian; Liu, Yi
A mild one-pot method for the direct conversion of aryl, heteroaryl and alkyl aldehydes into nitriles was achieved by forming the corresponding oximes in situ with NH2OH and allowing them to react with CuO and acetonitrile. Yields of the 13 nitriles prepared were moderate to very good (62–91%).